Exploration of acute and chronic anti-inflammatory potential of Quercus leucotrichophora A. Camus extracts in Wistar rats: A mechanistic insight - Saleem, Ammara; Hameed, Izza; Akhtar, Muhammad Furqan; Ashraf, Ghulam Md; Alghamdi, Badrah S.; Rahman, Md. Habibur; Almashjary, Majed N. (Frontiers in Pharmacology, 2023)
This research work was conducted to validate the folkloric use of Quercus leucotrichophora (QL) leaf extracts against inflammation and arthritis and to determine the chemical composition using HPLC. The aqueous and methanolic extracts of QL were evaluated by in-vitro anti-oxidant, anti-inflammatory (inhibition of protein denaturation and membrane stabilization) assays, and in vivo anti-inflammatory (carrageenan and xylene induced edema) models. For anti-arthritic potential, 0.1 ml Complete Freund’s Adjuvant (CFA) was inoculated to the left hind paw of a Wistar rat on day 1 and oral dosing with QL methanolic extract (QLME) at 150, 300, and 600 mg/kg was begun at 8th day till the 28th day in all groups except disease control that served with distilled water while methotrexate was given as standard treatment. There was a noteworthy (p<0.05-0.0001) restoration in body weight, paw edema, arthritic index, altered blood parameters and oxidative stress biomarkers in treated rats as compared to the diseased group. Moreover, QLME considerably (p<0.0001) downregulated TNF-α, IL-6, IL-1β, COX-2, and NF-κB, while significantly (p<0.0001) upregulated IL-10, I-κB, and IL-4 in contrast to diseased group. The QLME exhibited no mortality in the acute toxicity study. It was concluded that QLME possessed substantial anti-oxidant anti-inflammatory and anti-arthritic potential at all dosage levels prominently at 600 mg/kg might be due to presence of quercetin, gallic, sinapic and ferulic acid.